A solution to reduce overheating and increase wind turbine systems availability. Issue 3 (June 2021) - Singh, Gopal; Sundaram, Kalpathy; Matuonto, Marco
The ever-increasing demand for electrical power and the tremendous growth of renewable energy sources in the past decade has led designers to design wind turbine system components for optimal performance. Cost optimization, weight reduction, higher performances, and lower non-conformance cost are a few expectations that components are expected to meet in the present market condition. Wind turbine system unavailability impacts the annual energy production of the wind turbine. Overheating of the wind turbine system components is one of the main challenges to overcome. For the heating analysis, we discuss the wind turbine generator as a specific example in this article. This approach is equally valid for other components of wind turbine systems, with heat exchanger. Windings and bearings are the two main components susceptible to failure in the generator for wind turbine applications. The root cause may vary from case to case, but overheating accelerates the generator's windings and bearing failure and in many cases is the prime reason behind. Running the components at higher load points is one of the reasons for components to overheat. The article presents a solution to improve the performance of the wind turbine system and at the same time making it a commercially attractive choice. This can be achieved by reducing generator windings and bearings operating temperature, and also reducing its cost and weight at the same time. The proposed solution to reduce overheating is achieved and verified through results. The achieved results also explain how one solution is advantageous over the other.